##### Ad

related to**K.C**

Sort by

- Relevance
- |Time

...8x + 16 + y^2 - 2y + 1 + z^2 + 10z + 25 = 36 x^2 - 8x + y^2 - 2y + z^2 + 10z = -6 (

**c**) (6 - 4, -3 - 1, -1 - (-5)) = (2, -4, 4) = 2i - 4j + 4k2 Answers · Science & Mathematics · 29/04/2019

...an integer x = 2π - (π/6) + 2kπ x = (11π/6) + 2kπ x = π + (π/6) + 2kπ → where

**k**is an integer x = (7π/6) + 2kπ →**C**) answer4 Answers · Science & Mathematics · 11/06/2019

...point at which the derivative changes sign. This has ONE.

**C**) only for one particular value of**k**D) inflection point is a point on a continuous plane curve at which the curve...1 Answers · Science & Mathematics · 19/06/2019

... you, but when I see "decay constant", I think of the

**k**in this equation: A(t) = a e^(kt) Where A(t) is the amount...2 Answers · Science & Mathematics · 29/04/2019

(a) domain of f (-∞, ∞) (b) range of f [-1,∞) (

**c**) x-intercepts : 2 and 4 (d) y-intercept : 8 (e) f ...at x=3 (i) the relative minimum of f is -1 (j) f(-4) = 8 (**k**) The values of x for which f(x)=3 are 1...2 Answers · Science & Mathematics · 06/09/2019

Note the following: 1 - 2[1/2 + Ce^(-2t) ] = 1 - 1 - 2Ce^(-2t) = -2Ce^(-2t) = dy/dt Basically, you wanted to show that if we plug in the given y(t) into the right side of the equation, we get its derivative.

2 Answers · Science & Mathematics · 08/05/2019

...by 8 (x- (1/2))^2 - (y-1)^2/2 = 1 has center (h,

**k**) = (0.5, 1 ) semi major axis = a = sqrt(2) semi minor axis...sqrt(2) , 0) = (0.5 + sqrt(2) , 1) and (0.5 -sqrt(2) , 1 )**c**^2 =a ^2+ b^2 = 2 + 2**c**= 2 foci (2.5,1 ) and...4 Answers · Science & Mathematics · 29/04/2019

...the equation for the parabola in vertex form: y = (x - h)² +

**k**We have: y = x² + 6x + 10 To complete the...coefficient in front of x --> 6 b. Halve it --> 3**c**. Square it --> 3² = 9 d. Add it and...2 Answers · Science & Mathematics · 15/06/2019

##### Ad

related to**K.C**